Gender Inequity in the Clinical Setting - Fennern, Erin B.; Stein, Sharon L. (Clinics in Colon and Rectal Surgery, 2023)
Women in surgery continue to face inequitable treatment from surgical leadership, their peers, hospital staff, and even from their patients. Despite this, women surgeons continue to produce equal, or improved, clinical outcomes for their patients, with their work being given less remuneration than that of their male peers. The cultural stereotypes and biases that drive these inequities are implicit and subtle; however, they have dramatic effects on the lives and careers of women surgeons.
Keywords: gender bias; pay gap; homophily